ANALISIS TEKNIS DAN KELAYAKAN EKONOMI SISTEM PEMBANGKIT LISTRIK TENAGA PLTB TURBIN TULIP DAN PLTS MENGGUNAKAN SIMULASI HOMER PRO - I M Dwijaksana; I W Sukerayasa; I G N Janardana; C G I Partha C G I Partha; P A Mertasana; A A G M Pemayun (Jurnal SPEKTRUM, 2025)
The horizontal axis wind turbine in the smart microgrid system at DH Building, Faculty of Engineering, Udayana University, is not operating optimally due to blade damage. This study aims to evaluate the replacement of the horizontal wind turbine with a tulip-type wind turbine and to analyze its economic feasibility. Simulation and optimization were carried out using HOMER Pro software, considering the local wind and solar energy potential. The simulation results indicate an annual energy production of 103,205 kWh, with contributions from the PV system at 61.5% and the wind turbine at 38.5%. From an economic perspective, the project yields a Net Present Cost (NPC) of Rp 1,668,925,000, a Levelized Cost of Energy (LCoE) of Rp 4,368.36/kWh, and a Payback Period of 16 years and 8 months. The feasibility analysis results in a Net Present Value (NPV) of –Rp 308,312,810.02 and a Profitability Index (PI) of 0.7635. These findings demonstrate that the project is not financially feasible under the PLN tariff of Rp 1,699.53/kWh and a discount rate of 8.5%.